Caminho das águas na urbanização em Teresina, Piauí : da fundação ao sistema integrado de drenagem urbana - Lima, Maísa Veloso Rio (2017)
Since the beggining the occupation of the territory by man was linked to nature and natural resources: it removes nature from its source of survival. The world has never been so urban, for example, in the case of Latin America, more than 80% of the population lives in cities. This intense urbanization has brought significant impacts to urban ecosystems, altering their natural flows. Teresina, capital of Piauí, was designed and implemented in a place where its two rivers presence favored capital the economic growth. Teresina’s expansion remained respecting the natural water flows until 1950, when the country development policy provided a faster growth and a disorderly occupation of urban land. Demand for space, housing and urbanization altered Teresina water flow. This dissertation aims to describe and analyze the urbanization in Teresina and public actions regarding urban drainage aspects. The research was elaborated through a historical and documentary survey, and has as a spatial clipping the area of the sub-basin PE-31, characterized by its accelerated urbanization process and flooding. Urbanization and public actions resulted in hydrological cycle changes, causing environmental, social and economic impacts in Teresina.